STRATEGIES FOR IMPROVING EDUCATIONAL MANAGEMENT IN PRIMARY SCHOOLS (International journal of artificial intelligence, 2026)
This article explores strategies for improving educational management in primary schools. It discusses planning, leadership development, teacher collaboration, and the use of innovative technologies in school administration. The study emphasizes the importance of a systematic approach to management in achieving educational effectiveness.